Wednesday

April 23, 2014

April 23, 2014

Posted by **jack** on Tuesday, June 18, 2013 at 12:15pm.

- math -
**Steve**, Tuesday, June 18, 2013 at 3:00pmsince the roots are

-2/3 ±√23/3 i

1+α = 1/3 + √23/3 i

1+β = 1/3 - √23/3 i

(1+α)(1+β) = 1/9 + 23/9 = 24/9 = 8/3

**Related Questions**

Pure Mathematics - 4) The roots of the equation z^2+2z+4=0 are denoted by α...

math - Complex numbers α and β satisfy αα¯=ββ¯=&#...

Maths - Let α and β be the roots of 3x^2+4x+9=0. Then (1+α)(1+&#...

Math - If α and β are two angles in Quadrant II such that tan α...

Trigonometry - The quadratic equation x^2−9x+10=0 has roots tanα and ...

math - 1. Let α, β be the roots of the equation x2 - px + r = 0 and &#...

math - The roots of the polynomial f(x)=2x3+20x2+201x+2013 are α,β and...

Trig - prove sin(α+β)sin(α-β)=cos^2β-cos^2α please...

physics (speed of plane by radar) - The radar stations A and B, separated by the...

math - Is g = {(1, 1), (2, 3), (3, 5), (4, 7)} a function? Justify. If this is ...